2008
DOI: 10.1074/jbc.m708535200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of PTX3 Disulfide Bond Network and Its Multimeric Status in Cumulus Matrix Organization

Abstract: PTX3 is an acute phase glycoprotein that plays key roles in resistance to certain pathogens and in female fertility. PTX3 exerts its functions by interacting with a number of structurally unrelated molecules, a capacity that is likely to rely on its complex multimeric structure stabilized by interchain disulfide bonds. In this study, PAGE analyses performed under both native and denaturing conditions indicated that human recombinant PTX3 is mainly composed of covalently linked octamers. The network of disulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 54 publications
8
135
1
1
Order By: Relevance
“…Our findings indicate that the SCR19 -20 interacts with the N-terminal domain of PTX3, while the SCR7 binds the C-terminal domain, consistently with a previous report of CRP interacting with SCR7 (36). Furthermore, the lower level of binding of single PTX3 fragments in comparison to the full-length protein suggests the importance of structural organization of PTX3 into a full-size molecule and/or into polymers (51).…”
Section: ϫ7mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that the SCR19 -20 interacts with the N-terminal domain of PTX3, while the SCR7 binds the C-terminal domain, consistently with a previous report of CRP interacting with SCR7 (36). Furthermore, the lower level of binding of single PTX3 fragments in comparison to the full-length protein suggests the importance of structural organization of PTX3 into a full-size molecule and/or into polymers (51).…”
Section: ϫ7mentioning
confidence: 99%
“…structures (51), it is possible that PTX3 polymers can bind multiple FH molecules. Importantly, the multimeric nature of PTX3 could allow it to interact with more than one ligand at the same time.…”
Section: ϫ7mentioning
confidence: 99%
“…Moreover, it is involved in the modulation of the innate response associated with ongoing cell death (9,10) and interacts with the extracellular matrix, contributing to the assembly of the cumulus oophorus (11). PTX3 synthesis is a hallmark of vascular injury (12).…”
mentioning
confidence: 99%
“…5A). PTX3 is a multimeric protein composed of identical subunits linked by a network of disulfide bonds and high molecular masses (.50 kDa) correspond to not fully reduced PTX3 (39). In addition, we recently demonstrated that PTX3 is degraded by endogenous proteases (e.g., elastase), creating low molecular mass breakdown products (48).…”
Section: Ptx3 Contained In Maternal Milk Diffuses In Neonate Tissuesmentioning
confidence: 99%